2019
DOI: 10.3390/w11122493
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Manganese(II) from Acid Mine Wastewater: A Review of the Challenges and Opportunities with Special Emphasis on Mn-Oxidizing Bacteria and Microalgae

Abstract: Many global mining activities release large amounts of acidic mine drainage with high levels of manganese (Mn) having potentially detrimental effects on the environment. This review provides a comprehensive assessment of the main implications and challenges of Mn(II) removal from mine drainage. We first present the sources of contamination from mineral processing, as well as the adverse effects of Mn on mining ecosystems. Then the comparison of several techniques to remove Mn(II) from wastewater, as well as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 151 publications
0
24
0
Order By: Relevance
“…Additionally, these nanocomposites were used in that previous work for the removal of fluoride ions from aqueous solutions. In the present study, as a continuation to our research, we have applied the aforementioned nanocomposites as adsorbents for the removal of manganese(II) ions from aqueous media due to its high toxicity at higher concentrations than the permissible limits (8).…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, these nanocomposites were used in that previous work for the removal of fluoride ions from aqueous solutions. In the present study, as a continuation to our research, we have applied the aforementioned nanocomposites as adsorbents for the removal of manganese(II) ions from aqueous media due to its high toxicity at higher concentrations than the permissible limits (8).…”
Section: Resultsmentioning
confidence: 98%
“…Carrier-microencapsulation using ferric-catecholate complexes was investigated to mitigate pyrite oxidation and AMD generation (Li, Xu, Ma, & Hursthouse, 2019). Pyrite oxidation was suppressed by the electron-donating effects of the complexes, and coating formation on pyrite surfaces.…”
Section: Passive Treatmentmentioning
confidence: 99%
“…Various microorganisms can oxidize manganese, including bacteria, fungi, and algae (Greene and Madgwick, 1991;Li et al, 2019;Zhou and Fu, 2020). Previous studies revealed that some microalgae, such as Desmodesmus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Use of microalgae to generate BioMnO x has several advantages: it is environmentally friendly, and has higher efficiency and lower operation and maintenance costs than those of chemically (Li et al, 2019); however, some microalgae are sensitive to high manganese concentrations (Knauer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%